Determination of value : - Rosillo, Francisco (John Wiley & Sons Inc., 2013)
How to develop and support a credible opinion of value based on a foundational framework This book provides knowledge and guidance to valuation practitioners on achieving a new level of professionalism and credibility, as well as to those stakeholders in the valuation process in need of assessing the credibility of an appraiser's work product for decision-making purposes. It introduces a well defined framework of key credibility concepts and procedures at each step of the appraisal process, including reasonableness tests, valuation methodologies, financial analysis, economic and industry analysis, engagement planning, and informed judgment.